Implikacje utworzenia Europejskiej Służby Działań Zewnętrznych dla procesów kadrowych w polskiej służbie zagranicznej - Umińska-Woroniecka, Anna (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2014)
Establishment of the European External Action Service (EEAS) under the law of the Lisbon Treaty was one of the key changes in the institutional system of the Common Foreign and Security Policy (CFSP). Prospect of national diplomats recruitment to the EEAS seemed to be obvious for the member-states which joined the EU in 2004 and later, including Poland as the largest state among them. Taking into consideration this objective state of affairs, in her article the author tries to present genesis of the EEAS, its structure, the process of staff recruitment, extralegal conditioning of its operation, and finally Poland’s experience that results from its decennial operation within the EEAS system.
Keywords: Służba Działań Zewnętrznych; System Instytucjonalny Wspólnej Polityki Zagranicznej i Bezpieczeństwa Unii Europejskiej; równowaga geograficzna w ESDZ; równowaga płci w ESDZ